Effect of saline irrigation method on the growth of rice (Oryza sativa L.) - Adlian Adlian; Budiastuti Kurniasih; Didik Indradewa (Jurnal Ilmu Pertanian, 2020)
A field experiment was carried out to study rice growth under salinity stress in permanently flooded, intermittent, and saturated soil conditions. The experiment was conducted at field station of Faculty of Agriculture, Universitas Gadjah Mada located in Bantengan village, Banguntapan, Bantul, DIY, from August to November 2015. The treatments were arranged in a split-plot randomized complete block design, consisting of three irrigation methods as the main plot and two levels of salinity as the subplot, thereby resulting in six treatment combinations with three replications within each combination treatment. The three irrigation methods were permanent irrigation (flooded soil), intermittent irrigation (wet/dry soil), and irrigation above field capacity (saturated soil). The two levels of salinity were fresh water as control treatment (EC  0.3 dS.m-1) and saline water (EC  5 dS.m-1). The results of the experiment showed that there was no significant interaction effect of irrigation method and salinity on all observed rice growth variables. Salt stress negatively affected the rice growth, including plant height, plant dry weight, leaf area, and leaf area ratio (LAR). Irrigation method significantly affected plant dry weight and number of tillers at 3 and 9 weeks after planting. Permanent irrigation resulted in the highest plant growth compared to intermittent irrigation and above field capacity condition.